2009
DOI: 10.1002/fuce.200800134
|View full text |Cite
|
Sign up to set email alerts
|

Long Term Testing in Continuous Mode of HT‐PEMFC Based H3PO4/PBI Celtec‐P MEAs for μ‐CHP Applications

Abstract: Single cell and 500 We stack integrating Celtec P1000 MEAs were operated in continuous mode at 0.4 A cm–2 and 160 °C, under simulated reformate and air. Single cell's ohmic resistivity was almost unaffected by 1,100 h of ageing but the cell progressively switched from a cathodic to an anodic mass transfer limited operation. The stack was operated for 658 h, exhibiting the same behaviour and an additional increase in cell voltage distribution heterogeneity. CO2 proved to have negligible effect on performances b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(29 citation statements)
references
References 34 publications
0
27
0
Order By: Relevance
“…However, although necessary for better understanding of the aging mechanisms occurring in "real life" fuel cell systems, studies focusing on degradation at the stack level are far from numerous [5]. Particularly, heterogeneous degradation between the stack cells, that represents a major issue in PEMFC as system lifetime is often determined by the less effective cell, remains very little investigated [6,7]. Consequently, more information is needed on the individual behavior of each cell during long term stack testing, although time consuming as reported for instance by Cleghorn et al [8].…”
Section: Introductionmentioning
confidence: 98%
“…However, although necessary for better understanding of the aging mechanisms occurring in "real life" fuel cell systems, studies focusing on degradation at the stack level are far from numerous [5]. Particularly, heterogeneous degradation between the stack cells, that represents a major issue in PEMFC as system lifetime is often determined by the less effective cell, remains very little investigated [6,7]. Consequently, more information is needed on the individual behavior of each cell during long term stack testing, although time consuming as reported for instance by Cleghorn et al [8].…”
Section: Introductionmentioning
confidence: 98%
“…Mocoteguy et al [13] also observed that the high frequency loop disappears with increase in degradation, which makes it plausible to suggest that the disappearance of this loop is related to increased degradation from poisoning due to methanol.…”
Section: Overall Eismentioning
confidence: 93%
“…This is in agreement with the degradation rate claimed by BASF for the MEA. Mocoteguy et al [13] found a higher voltage drop rate of À41 mV/h over a period of 505 h on a Celtec-P1000 MEA, at a higher current density of 0.4 A/cm 2 and temperature of 160 C. In comparison, operation in the presence of 5% by volume of methanol-water vapor mixture in the anode feed gas shows a degradation rate of À900 mV/h, which is evidently deviated from the case of a pure hydrogen operation. Li et al [24] worked with reformate in their long-term durability tests with a voltage drop rate of À20 mV/h, which however cannot be directly compared with the current work as they used natural gas reformate.…”
Section: Overall Durabilitymentioning
confidence: 98%
“…The number of start/stop cycles is closely related to the overall lifetime of the fuel cell if the induced degradation effects are not mitigated. If, for instance, a HT-PEFC is used in a combined heat and power (CHP) [10][11][12] system, it is conceivable that several hundred cycles will be accumulated, which can lead to a rapid and irreversible damage of the stack. 13 It is necessary, therefore, to improve the understanding of the start/stop mechanism in order to deduce appropriate mitigation strategies.…”
mentioning
confidence: 99%